P–363 Poor Ovarian Response is Associated with Anti-ovarian Antibody, and Pro-inflammatory Immune Responses in Women Underwent Assisted Reproductive Technology Cycles. (6th August 2021) - Huang, C; Alsubki, L; Sung, N; Kwak-Kim, J
Abstract: Study question: To investigate if the anti-ovarian antibody (AOA) is associated with poor ovarian response (POR) and pro-inflammatory immune responses in women undergoing assisted reproductive technology (ART) cycles. Summary answer: The POR patients have a higher prevalence of AOAs. Women with autoimmune POR (POR(+)/AOA(+)) have dysregulated pro-inflammatory immune responses and metabolic factors. What is known already: It has been proved that AOAs play important role in diseases that related to human reproduction such as premature ovarian failure (POF) which also termed as premature ovarian insufficiency (POI), infertility, polycystic ovary syndrome (PCOS), in vitro fertilization (IVF) implantation failure, and in poor ovarian response in IVF stimulation. The POR women had elevated inflammatory immune responses: increased NK cell count and cytotoxicity, B cell counts, Th1/Th2 ratio and elevated metabolic factors such as higher homocysteine and plasminogen activator inhibitor–1 (PAI–1) level. Study design, size, duration: This study is a retrospective cohort study between December 2015 and February 2019. 248 women who underwent ART cycles were included. Study patients were divided into four groups based on AOA test and POR diagnose defined by the European Society of Human Reproduction and Embryology consensus: POR(-)/AOA (-) group (N = 148), POR(+)/AOA(-) group (N = 34), POR (-)/AOA (+) group (N = 44), POR(+)/AOA(+) group (N = 22). Peripheral blood was collected during the early follicular phase when they enter the program. Participants/materials, setting, methods: The natural killer (NK) cell levels and cytotoxicity, T helper (Th) 1/Th2 cell ratios were measured by flowcytometry. Anti-phospholipid Antibodies (APA) was tested by enzyme linked immunosorbent assay (ELISA). AOA, 25 (OH) vitamin D level, homocysteine, PAI–1 level was tested by Immunofluorescence Assay.One way ANOVA was applied to compare the continuous variables among study groups. Chi-squared analysis or Fisher's exact test were performed to compare the categorical variables. Main results and the role of chance: The POR patients have a significantly higher prevalence of AOA than non-POR patients (39.3% vs. 22.9%, P = 0.017, OR 2.176 95% CI 1.156–4.099). Peripheral blood CD56+ NK cell level (%), NK cytotoxicity, CD19+CD5+ B–1 cell level (%) and IFN-g/IL–10 producing Th1/Th2 cell ratios were significantly higher in POR(+)/AOA(+) group than those of other groups (P < 0.05, P < 0.05, P < 0.05, P < 0.05, respectively). TNF-a/IL–10 producing Th1/Th2 cell ratio of POR(+)/AOA (+) group was significantly higher than those of POR(+)/AOA(-) and POR(-)/AOA(-) groups (P < 0.05, respectively). Peripheral blood homocysteine and vitamin D levels of the POR(+)/AOA (+) group were significantly lower than those of other groups (P < 0.005, respectively). Peripheral blood PAI–1 level of POR(+)/AOA(+) group was significantly higher than that of POR(-)/AOA(-) group (P < 0.05). In POR(+)/AOA(+) group, the prevalence of antiphospholipid antibody was significantly higher than that of POR(+)/AOA(-) group (54.5% vs 20.5%, P = 0.005, OR 4.667, 95% CI 1.532–14.216). Limitations, reasons for caution: This was a single center study, results need to be validated across different center and study population. Wider implications of the findings: The diagnostic and therapeutic approaches for AOA (+) autoimmune POR patients should be differentiated from those for non-autoimmune POR. Trial registration number: Not applicable